Artificial Intelligence's Integration in Supply Chain Management: A Comprehensive Review - Dr. ABDAL AHMED, Dr. SHIKHA DABRAL, DURGESH BAHUGUNA, JASMEET KAUR, BHARTI SINGH, (European Economic Letters (EEL), 2023)
Supply chain management is a complex and dynamic field that requires efficient planning, coordination, and execution to meet customer demands while minimizing costs. In recent years, Artificial Intelligence (AI) has emerged as a disruptive technology with the potential to transform various aspects of supply chain management. This research paper provides a comprehensive review of the role played by AI in supply chain management, highlighting its applications, benefits, challenges, and future prospects. The paper discusses how AI can enhance supply chain visibility, demand forecasting, inventory management, logistics optimization, and risk mitigation. Furthermore, it explores the impact of AI on decision-making processes and collaboration within the supply chain network. The paper also addresses potential challenges and ethical considerations associated with the adoption of AI in supply chain management. By examining the current state of AI in supply chain management and analyzing its potential future developments, this research paper aims to provide valuable insights for practitioners and researchers in the field. This research study offers a thorough analysis of how artificial intelligence (AI) is used in supply chain management (SCM). AI has emerged as a disruptive technology that has the power to completely alter many different sectors, including SCM. This essay examines the use of AI in several elements of the supply chain, such as risk management, supplier selection, inventory management, and demand forecasting. The paper also discusses the benefits and challenges associated with implementing AI in SCM and highlights emerging trends and future directions in this field. By understanding the role of AI in SCM, organizations can leverage this technology to improve efficiency, reduce costs, and enhance overall supply chain performance.